Pengaruh Dana Pihak Ketiga dan Kekuatan Perusahaan Terhadap Harga Saham yang Dimoderasi oleh Risiko Keuangan - Yogaswara Tetra Putra; Fahrul Riza (Universitas Bunda Mulia, 2021)
This research was aimed to examine the effect of third party fund, firm’s strength (F-Score) moderated by financial distress (Z-Score) on the stock prices in banking sector throughout Covid-19 pandemic in Indonesia. The analysis used an independent variable of firm’s strength (F-Score), the control variable is third party fund, the moderating variable is financial distress (Z-Score). The dependent variable is stock prices. The sample of this research are firm’s financial report statement from listed company on Indonesian Stock Exchange. The sample was conducted by purposive sampling method and the sample as much 40 listed company and the statistical methode used was panel data analysis. The result of this research showed that firm’s strength didn’t significantly affect stock prices and was not moderated by financial distress (Z-Score). Third party fund significantly affect stock prices and was not moderated by financial distress (Z-Score). Third party fund didn’t significantly affect stock prices. This research used only samples from Indonesian Stock Exchange over pandemic covid-19 in Indonesia at the year of 2020. Further research could expand this research by doing it on another sector with another circumstances like corporate’s obligation or any other corporate’s action or using another variable such as debt to capital.